Insider Computer Fraud: An In-depth Framework for Detecting and Defending against Insider IT Attacks - Brancik, Kenneth (CRC Press, 2009)
An organization’s employees are often more intimate with its computer system than anyone else. Many also have access to sensitive information regarding the company and its customers. This makes employees prime candidates for sabotaging a system if they become disgruntled or for selling privileged information if they become greedy. Insider Computer Fraud: An In-depth Framework for Detecting and Defending against Insider IT Attacks presents the methods, safeguards, and techniques that help protect an organization from insider computer fraud.